Spatial aerodynamics of blunted cones in the presence of complicating factors in approach supersonic flow; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 2 - Pakhomov F. М. (Mathematics and mechanics. Physics, 2007)
Заглавие с титульного листа